Curating the soundtrack of the self a phenomenological study of musical identity negotiation on Spotify among University of the Philippines Diliman students - Japlit, Maria Isabel B.; Pacis, Agatha Beatrice T.
This study investigates how University of the Philippines Diliman (UPD) students negotiate their musical identities within Spotify’s digitally mediated environment. Drawing from Goffman’s Self-Presentation Theory, Hogan’s Exhibitional Approach, and the Musical Identities in Action (MIIA) framework, this research explores the interplay between individual agency, platform affordances, and socio-cultural factors. Semi-structured interviews with purposively selected students were analyzed using thematic analysis. Findings show that students actively co-create their musical identities through playlist curation, social sharing, and interactions with algorithmic features. However, cultural values such as pakikisama (social harmony) and hiya (sense of shame) shape their choices, creating tensions between global trends and local traditions. Aligned with Deuze’s media life perspective, Spotify is embedded in students' lives, mediating emotional regulation, social bonding, and identity expression. Students act as co-curators and cultural influencers, shaping their digital spaces to reflect and construct narratives of the self.